A treatment algorithm for the management of intraoral burns: A narrative review. Issue 5 (August 2018) - Kang, Steve; Kufta, Kenneth; Sollecito, Thomas P.; Panchal, Neeraj
Highlights: Intraoral burns are best treated by etiology — thermal, chemical, and electrical. Conservative modalities take precedence over surgical modalities in intraoral burns. Medical management of inflammation and pain is a priority. Preventive prostheses promote proper scar maturation and craniofacial growth. Surgery is reserved for debridement, oral contractures, and salivary duct injuries. Abstract: Oral mucosa follows a distinctly different trajectory of wound healing than skin. Although there are contemporary guidelines regarding treatment of burns to the skin, there is no standard of care specific to intraoral burns. This narrative review proposes an evidence-based treatment algorithm for the management of intraoral burns. Data was collated through a comprehensive review of the literature and only included studies that have reported particular success with favorable short- and long-term prognoses. In order to critically appraise the strength of the treatment recommendations, the GRADE criteria was applied to each arm of the algorithm. The algorithm was initially subdivided into the four primary etiologies of intraoral burns — thermogenic, cryogenic, chemical, electrical. Our findings emphasize the importance of conservative modalities of intra-oral burn treatment.